2013
DOI: 10.1534/genetics.113.153585
|View full text |Cite
|
Sign up to set email alerts
|

Viability, Longevity, and Egg Production of Drosophila melanogaster Are Regulated by the miR-282 microRNA

Abstract: The first microRNAs were discovered some 20 years ago, but only a small fraction of the microRNA-encoding genes have been described in detail yet. Here we report the molecular analysis of a computationally predicted Drosophila melanogaster microRNA gene, mir-282. We show that the mir-282 gene is the source of a 4.9-kb-long primary transcript with a 59 cap and a 39-poly(A) sequence and a mature microRNA of 25 bp. Our data strongly suggest the existence of an independent mir-282 gene conserved in holometabolic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…mir‐955 is not the only microRNA with possible importance in the regulation of reproduction and life‐history traits: miR‐282 has been associated with viability and egg production in Drosophila (Vilmos et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mir‐955 is not the only microRNA with possible importance in the regulation of reproduction and life‐history traits: miR‐282 has been associated with viability and egg production in Drosophila (Vilmos et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, three nonprotein coding genes were among the top candidates: mir-955 (a microRNA), CR43463 (a testes-limited gene), and CR43960. mir-955 is not the only microRNA with possible importance in the regulation of reproduction and lifehistory traits: miR-282 has been associated with viability and egg production in Drosophila (Vilmos et al 2013).…”
Section: Egg Retention Behavior In the Dgrpmentioning
confidence: 99%
“…Dnmt2 is also essential for the efficient functioning of Dicer-2 (Dcr-2) in Drosophila [44]. Infection with Wolbachia can disrupt the genome-wide patterns of cytosine methylation in Aedes aegypti [45]. Mosquitoes infected with the dengue virus induces expression of Dnmt2 while when mosquitoes introduced endosymbiont, Wolbachia , the expression of Dnmt2 is significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Third, all major epigenetic mechanisms (e.g., DNA methylation, histone modifications and non-coding RNA) are present in this fly model system [26], although DNA methylation in flies appears to be different from other eukaryotic organisms and present only at a very low level in adults [27, 28]. Clear evidence has demonstrated that histone modifications [13, 2932] and at least two microRNAs [33, 34] participate in the regulation of longevity. Finally, recent demonstration of nutritional programming of metabolism and longevity up to the F2 generation [11, 12] has revealed the post-eclosion adult stage to be suitable for assaying the epigenetic mechanisms underlying transgenerational programming of longevity in Drosophila .…”
Section: Introductionmentioning
confidence: 99%